(3GdHOGFY hGdCSQGQ aj MbjbI GdQO hGdCfJUGQ hZhGeV eG GLJeYJ Ydjg GdQeGI HGdCeUGQs
(3ChdgG (B:s
(3GdMeO ddg GdYGde HNajGJ GdCTQGQ GdeWdY Ydi eG LGd ai GdNhGWQ hGdCacGQ s
(3BNQgG (B:s
(3aEf GfcSQ dReg Gdjejf ai Pdc cdg hcPdc LejY eG TCfg eeG PcQfGg abS Ydjg JUH Ef TGA Gddg hdG Mhd hdG bhI EdG HGddg s
(3LGA Ydi UaMI GdYfhGf CfgG cJHJ HQSe GdebQ GdCTQa TYHGf hdYdg GdSdWGf TYHGf Hf eMeO Hf bdGhhf GdeJhai SfI (B747s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(32 / 1(3b(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs